High average power nonlinear self-compression to few-cycle pulses at 2 μm wavelength in antiresonant hollow-core fiber - Gebhardt, Martin; Gaida, Christian; Stutzki, Fabian; Jauregui, Cesar; Antonio-Lopez, Jose; Schulzgen, Axel; Amezcua-Correa, Rodrigo; Limpert, Jens; Tu¨nnermann, Andreas (Optics InfoBase Conference Papers, 2017)
We present the nonlinear self-compression of pulses from a high repetition rate thuliumdoped fiber laser system using a gas-filled antiresonant hollow-core fiber. Sub-3-cycle pulses with several GW peak power at 21.4 W of average power have been generated.
CRIS-Team Scopus Importer:2023-04-20